2017
DOI: 10.1364/boe.8.000555
|View full text |Cite
|
Sign up to set email alerts
|

Normalization of compression-induced hemodynamics in patients responding to neoadjuvant chemotherapy monitored by dynamic tomographic optical breast imaging (DTOBI)

Abstract: Abstract:We characterize novel breast cancer imaging biomarkers for monitoring neoadjuvant chemotherapy (NACT) and predicting outcome. Specifically, we recruited 30 patients for a pilot study in which NACT patients were imaged using dynamic tomographic optical breast imaging (DTOBI) to quantify the hemodynamic changes due to partial mammographic compression. DTOBI scans were obtained pre-treatment (referred to as day 0), as well as 7 and 30 days into therapy on female patients undergoing NACT. We present data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…The slow recovery in HbT as the breast is kept under compression, likely due to the steady decrease in compression force due to tissue relaxation, is consistent with our previous publications. 60,66 However, due to the complexity of the iterative DBT clinical breast positioning procedure, the optical image acquisition did not begin until ∼20 to 30 s after the breast tissue initially experienced compression. As a result, the early response is not captured in the presented data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The slow recovery in HbT as the breast is kept under compression, likely due to the steady decrease in compression force due to tissue relaxation, is consistent with our previous publications. 60,66 However, due to the complexity of the iterative DBT clinical breast positioning procedure, the optical image acquisition did not begin until ∼20 to 30 s after the breast tissue initially experienced compression. As a result, the early response is not captured in the presented data.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, using a standalone dynamic optical imaging system with a computer controlled compression mechanism, we have seen an early decrease in tumor HbT during compression. 60,66 However, in the example TOBI2 scan, this early decrease has likely occurred before the measurement was initiated (while the radiology technician was positioning the breast under compression to match clinical standards). The significantly larger decrease in tumor HbT observed after the transition to full compression versus the surrounding normal tissue (likely related to the higher stiffness of tumor tissue) may be a useful tumor marker and will be further characterized in future work.…”
Section: Discussionmentioning
confidence: 99%
“…DOSI measures absolute concentrations of oxyhemoglobin, deoxyhemoglobin, lipid, and water. These parameters have been shown by multiple research groups to be valuable prognostic markers at various points throughout NAC [6,9,16,21,27,45,46,48,49,50,53]. For example, a recent landmark multicenter study (ACRIN 6691) showed that changes in tumor deoxyhemoglobin, water, and lipid at midpoint of NAC correlated strongly to pCR [48].…”
Section: Introductionmentioning
confidence: 99%
“…These reconstructed quantities have been shown to discriminate between malignant and healthy tissue in the breast (Srinivasan et al 2005, Spinelli et al 2005, Cerussi et al 2006, Choe et al 2009, Wang et al 2010, Fang et al 2011, Mastanduno et al 2014). Importantly, several studies have employed DOSI techniques to investigate functional changes in malignant tissue over the course of NAC and have correlated these changes with the patients’ responses to treatment (Choe et al 2005, Tromberg et al 2005, Zhou et al 2007, Cerussi et al 2007, Zhu et al 2008, Jiang et al 2009, Soliman et al 2010, Cerussi et al 2011, Roblyer et al 2011, Falou et al 2012, Ueda et al 2012, Choe and Durduran 2012, Busch et al 2013a, Tromberg et al 2016, Sajjadi et al 2017). The present paper is focused on another diffuse optical technique, diffuse correlation spectroscopy (DCS), which utilizes the temporal fluctuations of detected light intensity to probe microvasculature blood flow in deep tissue (Durduran et al 2010).…”
Section: Introductionmentioning
confidence: 99%